Artistic exploration of national song arrangement through twelve-tone techniques for guitar ensemble: impact on higher education music learning - Kustap, Kustap (International Journal of Visual and Performing Arts, 2025)
This study addresses a pedagogical challenge in higher education, namely the lack of instructional materials for guitar ensemble courses. This issue has been identified in the Music Department of ISI Yogyakarta, where students encounter difficulties engaging with classical Western music materials due to unfamiliarity, particularly among those without prior training in formal music education or vocational music programs. To mitigate this challenge, arrangements of Indonesian national songs are introduced as a strategic approach, leveraging their familiarity to enhance student engagement and motivation in ensemble practice. This study arranges Bangun Pemudi Pemuda, a national song selected for its rhythmic and melodic qualities that lend themselves well to classical guitar ensemble performance. The arrangement employs four distinct voices, mirroring choral harmonization. A key innovation in this arrangement is the incorporation of the dodecaphonic scale, designed to introduce students to modern arrangement techniques, specifically the twelve-tone series. This research adopts an artistic research methodology, encompassing the arrangement process and its implementation in guitar ensemble classes. The qualitative dimension is examined through focus group discussions (FGDs), literature reviews, and classroom observations, fostering dialogue and interaction. This study aims to develop instructional materials that support students in cultivating classical guitar proficiency, ensuring that the applied techniques contribute to their technical advancement while utilizing national songs as an accessible entry point for learning.